Fostering Digital Citizenship in Indonesia - Triastuti, Rini (Proceeding of International Conference on Teacher Training and Education, 2016)
This article is intended to illustrate the importance of raising awareness of digital citizenship in Indonesia. The rapid development of technology has penetrated all over the world, including Indonesia. It has influenced the behavior of Indonesian citizens. On the other hand the media often describes the news related to the misuse of technologies such as spreading pornographic content, defamation via social media and so on. Based on those things it needs for an effort to raise awareness of digital citizenship to the Indonesian citizens. We realize that today we do not only face the real world but also the digital world, where the digital world as important as the real world. Even in everyday life we can not be separated from the digital world. With presence of digital citizenship awareness of the digital technology users in Indonesia users can behave as expected. That awareness can be suggested to revise through education, currently Indonesia concern with character education. It is therefore appropriate that fostering awareness of digital citizenship is also needed to get a part in character education for IndonesianÂ citizens.